2021
DOI: 10.47162/rjme.62.3.07
|View full text |Cite
|
Sign up to set email alerts
|

E-cadherin, fibronectin and Slug immunoexpression in non-melanoma skin cancers

Abstract: Epithelial-mesenchymal transition (EMT) is an essential biological process involved in the initiation and progression of cancer by which epithelial tumor cells lose their differentiated characteristics, such as cell-cell adhesion and apical-basal polarity and acquire a more invasive and/or metastatic mesenchymal phenotype. The present study investigated the expression of immunomarkers with a role in EMT of nonmelanoma skin cancers (NMSCs), such as E-cadherin, fibronectin and Slug, for a number of 50 NMSCs, rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…The loss of epithelial markers and the acquisition of mesenchymal features are achieved through complex mechanisms involving different signaling pathways, transcription factors, altered expression of adhesion molecules, reorganization of cytoskeletal proteins, and production of extracellular matrix-degrading enzymes [ 22 , 23 , 26 , 27 , 90 ]. The activation of p38 MAPK, AKT, and ERK signaling plays an important role in the EMT process [ 23 , 26 , 74 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The loss of epithelial markers and the acquisition of mesenchymal features are achieved through complex mechanisms involving different signaling pathways, transcription factors, altered expression of adhesion molecules, reorganization of cytoskeletal proteins, and production of extracellular matrix-degrading enzymes [ 22 , 23 , 26 , 27 , 90 ]. The activation of p38 MAPK, AKT, and ERK signaling plays an important role in the EMT process [ 23 , 26 , 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…The progression of the skin carcinogenesis process is characterized by the occurrence of the epithelial–mesenchymal transition (EMT), a complex biological mechanism in which epithelial tumor cells tend to lose their differentiated properties (loss of E-cadherin, desmoplakin, and laminin-1 expression) and redirect to a mesenchymal-like phenotype (increased expression of N-cadherin, vimentin, fibronectin, MMP-2), with a consequent increase in their migratory and invasive potential [ 22 , 23 , 24 , 25 , 26 , 27 ]. Increasing evidence demonstrates that metabolic reprogramming is a hallmark of cancer and extensive metabolic dysregulation of cancer cells is related to the EMT program [ 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, premature senescence was found in the fibroblasts of vitiligo skin, which, despite experiencing a greater production of fibronectin, does not exert the usual barrier function, resulting in impaired cell adhesion [79]. In this same study, it was observed that fibroblasts secrete and release growth factors associated with skin aging, such as the hepatocyte growth factor (HGF) and inflammatory cytokines such as interleukin 1-beta (IL-1b), which controls the functionality of melanocytes, negatively regulating the expression of E-cadherin and impairing the integrity and architecture of epithelial tissue [80].…”
Section: Skin Senescencementioning
confidence: 99%
“…BCCs are the most common neoplasms, not only of the skin but of the entire human body, occupying the first place among nonmelanoma skin cancers (NMSCs) (70%), followed by squamous cell carcinomas (25%) [32]. Despite being about three times more common than SCC, BCC does not cause high mortality because it rarely metastasizes with an incidence of 0.0028-0.55% [33].…”
Section: Basal Cell Carcinomamentioning
confidence: 99%